Program Evaluation Supplementary Feeding in Overcoming Stunting in Tieng Village - Lathifah, Eva Nasyiatul; Fitriyah, Qonitah Faizatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Nutrition and health problems in early childhood are important factors in the process of child growth and development and require serious attention from parents and educators. The Central Leadership of Nasyiatul Aisyiyah implements the TIMBANG (Improve Balanced Nutrition) Program in Tieng Village as one of the stunting locus areas in Wonosobo Regency. Based on preliminary data, the prevalence of stunting in Tieng Village reached 30%, far above the WHO standard of 22%. This study aims to evaluate the implementation of the 12-day supplemental feeding program for stunted toddlers in Tieng Village. The research used a descriptive qualitative approach with informants consisting of the Central Leadership of Nasyiatul Aisyiyah, village heads, TIMBANG coordinators, village midwives, human development cadres, and stunting mothers under five. Data was collected through in-depth observation and interviews. The results of the study showed that the program was running according to standards and no significant obstacles were found. The program has succeeded in reducing the number of stunting toddlers from 110 to 76 children. These findings show that the provision of additional food has a positive impact in accelerating stunting reduction so that the village government is expected to allocate a budget for the sustainability of the program.